sqrt(5t+3)=-2

Simple and best practice solution for sqrt(5t+3)=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for sqrt(5t+3)=-2 equation:


Simplifying
sqrt(5t + 3) = -2

Reorder the terms:
qrst(3 + 5t) = -2
(3 * qrst + 5t * qrst) = -2
(3qrst + 5qrst2) = -2

Solving
3qrst + 5qrst2 = -2

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Reorder the terms:
2 + 3qrst + 5qrst2 = -2 + 2

Combine like terms: -2 + 2 = 0
2 + 3qrst + 5qrst2 = 0

The solution to this equation could not be determined.

See similar equations:

| 0.75(4+d)=13.5 | | 3x-2(x-3)=15 | | 4x-3(3x-8)=4(3x-7)+8x | | 0.333(-3)+-5= | | N+20=11 | | 4u-24=2(u-5) | | -6m+14-8m=25m+341 | | 7x-10+2x=-19 | | -200=-4(1+7x) | | u+4/5=73/4 | | 15a-(-44)=46 | | 10-3x-6-12x=7 | | 23-6x=16+x | | 5(5-8x)=-39-8x | | 2x-(x+2)=4-x | | k/-9+5=-4 | | (y-4)/2=10 | | 10.80/18 | | 15-8x=-3-1-7x | | 245.76-m=75.00 | | 54=n-89 | | -6(1+8r)-7r=434 | | 1/3(-3)+5=-16 | | 16=5+7x | | -13-3X-2+5X=1+6X-2X | | 2(x+4)=23 | | 6(-7)+(-5)-(-2)= | | v=x(10-2x)(15-2x) | | 3x-1x+5=55 | | (-13)-8= | | -168=6(8b-4) | | -1/5+3x=7 |

Equations solver categories